Устройство для сбора просыпей таблеток отработавшего ядерного топлива - Гаврилов П. М. Петр Михайлович; Ревенко Ю. А. Юрий Александрович; Бараков Б. Н. Борис Николаевич; Федосов Ю. Г. Юрий Георгиевич; Гамза Ю. В. Юрий Вячеславович; Рыбалкин И. А. Игорь Андреевич
опубл. 10.03.12